A SYNTACTICAL ANALYSIS ERROR ON STUDENTS’ GRAMMAR THROUGH TREE DIAGRAM - Ika Nuriyanti (IKIP Siliwangi, 2022)
Writing skill is one of four language skill in English. Writing include the grammar. According to this fact this study aims to find out analysis error on students’ grammar through tree diagram. The Method used in this research that suit with the analysis is qualitative design. The data was collected by observation, interview and document. From the most error, the researcher classified the students’ grammatical errors, they are simple past tense, there are some past verbal sentence, Nominal sentence, Possessive Pronoun, Gerund, and modal. From 30 students who became the sample, there were some students made errors in simple past tense with the percentage 83,3%. And precentage 13,85 in gerund. And in possossive pronoun 27,7%. and in nominal sentence is precentage 22,2% . Here can be conclude that tree diagram is recommended to analyze students’ grammar. Keywords: Syntax, Analysis Error, Grammar, Tree Diagram